Comparative field study of spring and summer leaf gas exchange and photobiology of the mediterranean trees Quercus ilex and Phillyrea latifolia - Penuelas, J.; Filella, I.; Llusia, J.; Siscart, D.; Piñol, J. (Journal of Experimental Botany, 1998)
Summer-induced changes in gas exchange, fluorescence and reflectance were measured on leaves of two co-occurring Mediterranean small trees, Quercus ilex and Phillyrea latifolia, in May, June and July 1996 in Central Catalonia (NE Spain). The humid 1996 summer only produced mild water stress conditions. However, photosynthesis (A) and stomatal conductance (gs) decreased in June and July in both species. In June P. latifolia had higher net photosynthetic rates and lower stomatal conductances than Q. ilex, thus exhibiting higher instantaneous plant water use efficiencies. In agreement with these results, the photo-chemical reflectance index (PRI, calculated as (R570-R531)/(R531+R570)) of P. latifolia was lower, suggesting a possible lower xanthophyll de-epoxidation state. However, P. latifolia had lower ΔF/F′ and therefore a lower electron transport rate (ETR). The behaviour of PRI confirmed previous studies indicating a strong relationship between PRI, ΔF/F′ , and photosynthetic radiation-use efficiency (PRUE). PRI offers a simple, portable means of assessing PRUE with the potential for remote sensing applications. Finally, the possible ecological consequences of these results on the behaviour of the two species studied under the predicted warmer and drier conditions of global change are discussed.
10.1093/jxb/49.319.22910.1093/jxb/49.319.229
Keywords: fluorescence; intrinsic water use efficiency; net photosynthetic rates; phillyrea latifolia; photochemical efficiency; photochemical reflectance index; photosynthetic radiation-use-efficiency; Quercus ilex; reflectance; Stomatal conductance; summer; water index

Leaf gas exchange and ﬂuorescence of Phillyrea latifolia, Pistacia lentiscus and Quercus ilex saplings in severe drought and high temperature conditions - Filella, I.; Llusia, J.; Piñol, J.; Penuelas, J. (Environmental and Experimental Botany, 1998)
Saplings of Phillyrea latifolia, Pistacia lentiscus and Quercus ilex were witheld watering for 7 days, followed by reirrigation. Incident photosynthetic photon ﬂux density (PPFD), leaf temperature, net photosynthetic rates, stomatal conductance, and photochemical efﬁciency of the photosystem II (DF:F’m) were measured three times during the day. The watered plants had higher photosynthetic rates, stomatal conductances, DF:F’m and ETR than non-watered plants. However, watered plants were mildly water stressed as shown by low ratio of variable to maximal ﬂuorescence (Fv:Fm) and high non-photochemical ﬂuorescence quenching (qN). Their DF:F%m was low in the morning and increased in the evening, following the variations in PPFD. Watered plants of Q. ilex had lower photosynthetic activity, stomatal conductance and photosynthetic radiation use efﬁciency than Ph. latifolia and P. lentiscus, and, conversely, reached the highest DF:F%m and ETR. This seems to indicate a different relationship between photosynthetic activity and electron transport rate in Q. ilex compared to the other two species. Ph. latifolia and P. lentiscus appeared to be better adapted to severe drought than Q. ilex.
Keywords: Drought; hF/F’m; phillyrea latifolia; photosynthetic rate; Pistacia lentiscus; Quercus ilex; Stomatal conductance